(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The problem of language in society is directly reflected in the level of language proficiency of students studying in higher educational institutions. Not even talking about their literacy in the Kyrgyz language, the level of communication does not meet the requirements of the time. Today, the main goal of teaching Kyrgyz as a second language is to increase the vocabulary of students, the formation of communication competence, the development of the ability to freely express one’s thoughts, teach fluency, conduct office work in the national language, and also teach to write competently, read correctly. And when teaching the Kyrgyz language in universities, courses aimed at this goal should be held, which should lead to effective results. The article presents the stages, goals, course and results of using the «Lesson-Theater» method, which led to positive and fruitful results.